Quadrotor system for gathering discomfort index and amount of air pollutants - Cheong, Junlae (Animo Repository, 2017)
© 2017 IEEE. One can often feel some form of discomfort when going outdoors either from the heat or from the pollutants present in the air such as humidity, temperature, and the presence of air pollutants such as carbon monoxide and particulate matter. In the national setting, there has not been much awareness of the factors of discomfort yet these still prevail. The proposed solution for this problem is a system that is able to measure different parameters of discomfort. To provide safety for the measurer and the mobility of the system, the group has implemented the system on an unmanned aerial vehicle, specifically, a quadrotor. Here, the controller can manipulate the quadrotor system to go up at a desired altitude for measurements. This has been tested quarterly during the daytime and is able to maintain 85% accuracy but during testing, this may not be the case since there are other external factors that can affect the measurements such as the input power and wind. An Android application has been developed for the purpose of updating and viewing the data recorded.